Transition From Hand-Assisted to Pure Laparoscopic Donor Nephrectomy - You, Dalsan (JSLS, 2015)
BACKGROUND AND OBJECTIVES: We compared perioperative donor outcomes and early graft function of hand-assisted laparoscopic donor nephrectomy (HALDN) and pure laparoscopic donor nephrectomy (PLDN) performed by a single surgeon, to define the feasibility of technical transition from HALDN to PLDN. METHODS: From October 1, 2012, through June 30, 2014, 60 donor nephrectomies were performed by a single surgeon who lacked experience with laparoscopic renal surgery: the first 30 by HALDN and the last 30 by PLDN. Operative and convalescence parameters were compared, as were intra- and postoperative complications within 90 days according to the Satava and Clavien-Dindo classifications, respectively. Binary logistic regression analysis was used to estimate the association of baseline characteristics with complications. RESULTS: Baseline characteristics were similar in the 2 groups, except for American Society of Anesthesiologists score II (10.0% vs 43.3%; P = .007). All procedures were completed as planned. All operative and convalescence parameters of donors and graft outcomes were similar in the 2 groups, as were overall rates of intraoperative (43.3% vs 36.7%, P = .598) and postoperative (86.7% vs 70.0%; P = .209) complications. No factor was significantly predictive of intraoperative complications, whereas sex (female vs male, odds ratio, 0.183; P = .029) and learning curve (odds ratio, 0.602; P = .036) were significant determinants of postoperative complication. CONCLUSION: The technical transition from HALDN to PLDN does not involve a steep learning curve for surgeons less experienced with laparoscopic renal surgery and maintains similar perioperative donor and graft outcomes.